2016
DOI: 10.1007/978-3-319-45234-0_19
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Facebook Adoption Among Young Adults in a Northeastern State of India: Validation of Extended Technology Acceptance Model (TAM)

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Basak and Calisir (2015) assert that the user can be entertained through the exchange of information, watching videos, listening to music, playing online games, as well as seeing other user's profile. Several researchers have investigated the impact of intrinsic motivation or hedonic motivation on the users' intention to use new technologies (e.g., Alalwan et al, 2014;Alryalat et al, 2016;Abed, 2016). In the SNS context, few studies have examined the role of HM on behavioural intention (Basak and Calisir, 2015;Mouakket, 2015;Yoon and Rolland, 2015;Hsiao et al, 2016) and even fewer in using SNS for educational purposes (Hamid et al, 2015;Sharma et al, 2016).…”
Section: Hedonic Motivation (Hm)mentioning
confidence: 99%
“…Basak and Calisir (2015) assert that the user can be entertained through the exchange of information, watching videos, listening to music, playing online games, as well as seeing other user's profile. Several researchers have investigated the impact of intrinsic motivation or hedonic motivation on the users' intention to use new technologies (e.g., Alalwan et al, 2014;Alryalat et al, 2016;Abed, 2016). In the SNS context, few studies have examined the role of HM on behavioural intention (Basak and Calisir, 2015;Mouakket, 2015;Yoon and Rolland, 2015;Hsiao et al, 2016) and even fewer in using SNS for educational purposes (Hamid et al, 2015;Sharma et al, 2016).…”
Section: Hedonic Motivation (Hm)mentioning
confidence: 99%
“…Most of the studies presented in this systematic have pointed out some research gaps and hence have suggested there are areas or areas for further investigation. For example, most studies have cited generalization as a major drawback [57], [58]. Generalization for populations other than those in the study sample presented is discouraged due to specific demographic or cultural contexts.…”
Section: B Gaps In Current Work and Implications For Future Researchmentioning
confidence: 99%
“…Several researchers have investigated the impact of intrinsic motivation or hedonic motivation on the users' intention to use new technologies (e.g. Alalwan et al, 2014;Alryalat et al, 2016;Abed, 2016). In the SNS context, few studies have examined the role of HM on behavioural intention (Basak and Calisir, 2015;Mouakket, 2015;Yoon & Rolland, 2015;Hsiao et al, 2016) and even fewer in using SNS for educational purposes (Hamid et al, 2015;Sharma et al, 2016).…”
Section: Hedonic Motivation (Hm)mentioning
confidence: 99%